Mustan auringon paketti : myytti ja melankolia Irene Larsenin kokoelmassa Sortsolsafari - Ahvenjärvi, Kaisa (AVAIN - Kirjallisuudentutkimuksen aikakauslehti, 2015)
In this article, I analyse how the Sámi poet Irene Larsen rewrites Sámi oral tradition and mythology in her collection Sortsolsafari (2013, “Black Sun Safari”). I discuss how Larsen’s work differs from the mainstream of contemporary Sámi poetry and other indigenous literatures. Sortsolsafari has postmodernist features, which seldom are found in Sámi literature. Larsen situates mythological elements in present-day reality: a Sámi goddess uses a sewing machine and a shaman logs on to the Internet. These anachronisms create a comical effect. Instead of nostalgia and anti-colonialism, which traditionally characterize the depiction of the past in Sámi literature, the overall tone of Sortsolsafari is melancholic and tragicomic. In contemporary Sámi poetry, fragments of mythology are often used to construct the unity of the Sámi people. Larsen’s poems lack this collective, emancipatory dimension. Larsen uses Sámi mythology and tradition to express the speaker’s individual experience of loss and detachment. The sun, which is the mythical forefather and a collective national symbol of the Sámi, has become the black sun of depression. Instead of relying on national-romantic nostalgia Larsen constructs the past by using banal anachronisms and individual melancholia. peerReviewed